Turning point in a system of differential equations with analytic operator - Bobochko, V. N. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We construct uniform asymptotics for a solution of a system of singularly perturbed differential equations with turning point. We consider the case where the boundary operator analytically depends on a small parameter.